Analisis Tindak Tutur Lokusi, Ilokusi dan Perlokusi Dalam Acara Podcast Log In X Close The Door - Nur Lenasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study is motivated by speech acts in internal language podcast Habib Husein Ja'far, Onadio Leonard, and Steve Marcel entitled